MST1 Promotes Apoptosis through Regulating Sirt1-dependent p53 Deacetylation - Yuan, Fang (American Society for Biochemistry and Molecular Biology, 2011)
Mammalian Sterile 20-like kinase 1 (MST1) protein kinase plays an important role in the apoptosis induced by a variety of stresses. The MST1 is a serine/threonine kinase that is activated upon apoptotic stimulation, which in turn activates its downstream targets, JNK/p38, histone H2B and FOXO. It has been reported that overexpression of MST1 initiates apoptosis by activating p53. However, the molecular mechanisms underlying MST1-p53 signaling during apoptosis are unclear. Here, we report that MST1 promotes genotoxic agent-induced apoptosis in a p53-dependent manner. We found that MST1 increases p53 acetylation and transactivation by inhibiting the deacetylation of Sirtuin 1 (Sirt1) and its interaction with p53 and that Sirt1 can be phosphorylated by MST1 leading to the inhibition of Sirt1 activity. Collectively, these findings define a novel regulatory mechanism involving the phosphorylation of Sirt1 by MST1 kinase which leads to p53 activation, with implications for our understanding of signaling mechanisms during DNA damage-induced apoptosis.